A structural equation modelling approach to investigating the impact of academic, ICT and management related factors on customer satisfaction in higher education - Jager, Johan W de; Jan, Muhammad Tahir (National Academy of Management, 2016)
This study focuses on the influence of academic factors, the role of ICT and management on customer satisfaction. The sample of 391 students from two universities in South Africa was chosen random to participate in the study. Exploratory Factor Analysis (EFA) was used followed by Confirmatory Factor Analysis (CFA), and finally Structural Equation Modelling (SEM). Management-related factors resulted with the strongest significant impact on customer satisfaction followed by academic factors.